DPRD Political Communication in Improving Legislative Role in Malang City (Study at the Malang City DPRD Office on Commission A) - Reynaldi Afifta Pratama; Asep Nurjaman (Budapest International Research and Critics University, 2022)
Considering the role and function of DPRD, one of which is DPRD Malang City, it is very important, then the political communication of DPRD as an institution to the community cannot be ruled out, the aim is none other than to increase the role of the legislature itself. The DPRD's political communication in enhancing the legislative role in Malang City is no exception. Political communication carried out by the Malang City DPRD in increasing the legislative role in Malang City, is carried out by communicating directly with the public who are usually represented by certain elements of society. The strategy used in delivering political communication is carried out in various ways, starting from planning, delivering messages, and managing political communication media. In managing political communication messages, the management of strategic political issues is still minimally carried out by the Malang City DPRD, they also rarely appear in the mass media and news about the Malang City DPRD is also very minimal. To overcome this, the Malang City DPRD uses social media to communicate that is not conveyed through the mass media. Meanwhile, the media used in delivering political communication to the Malang City DPRD is carried out in various ways, either directly, using mass media which are considered to be able to reach the community. wider. Malang City DPRD also has official communication media such as Website, Facebook, Instagram, and Twitter. Through these media, Malang City DPRD conveyed information related to their legislative function as people's representatives.